Efficiency of Multi-Level Governance and Common EU Security and Defence Policy under Conditions of Hybrid Threats - Karamyshev, Dmytro; Suvorov, Valentyn (Pressing Problems of Public Administration, 2024)
The article substantiates and proves that the focus on the implementation of the common policy and global strategies of the EU regarding the construction of a new European model of multi-level governance, strategic security and stability requires both the agreement of all decision-making subjects and ensuring their effectiveness in the conditions of global influences and hybrid threats. For the first time, the main provisions of the three-level conceptual model of rationalization of multi-level management are formulated and its use in the implementation of European security and defense policy in the context of hybrid threats is formulated, taking into account the relevant elements of sequence in the formation and implementation of public policy, which can significantly optimize the determination of the degree of integration by an individual participating country , willingness to invest and the ability to develop a specific strategic direction within the EU, as well as other ways and means of achieving its goals, algorithmization and demonstration of a step-by-step algorithm for solving complex problems to the subjects of implementation of programs and projects, as components of a complex coordination mechanism in the system multi-level management. Emphasis is placed on increasing the effectiveness of the implementation of the common security and defense policy of the EU in the conditions of hybrid threats and the need to introduce an integrated approach to ensure the national stability of European countries based on the concept of multi-level management, taking into account the global strategies of the EU.